2016
DOI: 10.18865/ed.26.1.99
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Metabolic Syndrome and its Related Risk Factors in the City of Oran, Algeria: the ISOR Study

Abstract: <p><strong>Background</strong>: Aging and lifestyle changes had led to an  epidemiological transition, with a significant impact on the incidence of cardiovascular diseases in North Africa. <br /><strong></strong></p><p><strong>Objective</strong>: The aim of this study was to determine the prevalence of metabolic syndrome and its associated factors, which were unknown, among an urban population in Algeria.</p><p><strong>Methods:</… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
17
0
5

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 42 publications
5
17
0
5
Order By: Relevance
“…As shown in Fig. 4, the 1st line is the standard scale compared to each downward line (2)(3)(4)(5)(6)(7), by which a specific score of each line could be calculated. Then sum of 6 lines (scores) will be put on the 8 th line as the total points, and projected to the last line, which stands for the possibility of MetS.…”
Section: Correlation Between Components Of Mets and Independent Risk mentioning
confidence: 99%
See 1 more Smart Citation
“…As shown in Fig. 4, the 1st line is the standard scale compared to each downward line (2)(3)(4)(5)(6)(7), by which a specific score of each line could be calculated. Then sum of 6 lines (scores) will be put on the 8 th line as the total points, and projected to the last line, which stands for the possibility of MetS.…”
Section: Correlation Between Components Of Mets and Independent Risk mentioning
confidence: 99%
“…Meanwhile, MetS-related risk factors vary in previous different researches, yet consensus was reached that variables-age, body mass index, socioeconomic (household income, education level et al) and lifestyle characteristics (physical activity, smoking et al) were defined as risk factors 4 . Recently, a systematic review and meta-analysis revealed anxiety is associated with MetS 5 .…”
mentioning
confidence: 99%
“…Hence, they suggested cigarette cessation and dietary pattern modi cation to be the major prevention strategies in controlling MetS. Other study reported that intermediate level of physical activity seemed to be a protected factor of MetS [26]. Therefore they claimed that there was need for prevention strategies involving promotion of physical activity.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of MetS differs according to several parameters: definition, country, sex, age, and even according to the region in the same country. In Algeria, a recent study shows that the prevalence of metabolic syndrome was 20 % in the Oran population, it was higher in women than men (25.9 vs 13.7 %) (Houti et al, 2016).…”
Section: Introductionmentioning
confidence: 94%